Explaining the positioning of agricultural entrepreneurs on the necessity-opportunity continuum in sub-Saharan Africa: insights from Benin - Thoto, F.S.; Mignouna, Djana B.; Adeoti, R.; Gbedomon, R.C.; Chogou, S.K.; Aoudji, A.; Honfoga, B. (Informa UK Limited, 2024)
Despite the potential of agriculture to reduce unemployment in sub-Saharan Africa, research on agricultural entrepreneurship is scarce, especially regarding the entrepreneurs’ motivations. The aim of this research is to examine the intensity of necessity and opportunity motivations among agricultural entrepreneurs and the influence of socioeconomic characteristics, personality, and environmental factors. Hence, the study reports a survey of 819 agricultural entrepreneurs in Benin and uses multinomial logistic regressions. Most agricultural entrepreneurs are moderately necessity-driven (76%); the remainder includes highly necessity-driven entrepreneurs (4%), moderately opportunity-driven entrepreneurs (6%), and highly opportunity-driven entrepreneurs (14%). Those displaying higher intensity of necessity motivations can be at any education level, are former employees, are less proactive, less optimistic, and operate in the services sector. In contrast, highly opportunity-driven entrepreneurs are likely to have received a university education and agricultural professional training, operate in the services sector, and have better access to finance and technologies. This study advances the push-pull theory by revealing a richer set of entrepreneurial motivations beyond the simplistic dichotomic view. Hence, policymakers could devise entrepreneurship strategies and programs that consider the diverse motivations of entrepreneurs and the influencing factors to move them toward increased opportunity entrepreneurship.